NAHWU AL-FARRA’S THOUGHTS IN SURAH AL-MULK’S IN THE BOOK OF MA’ANI AL-QUR’AN LINGUISTIK MADZHAB STUDY - Nashihah, Halimatun; Habib, Moh.; Nulhakim, Lukman (Hijai - Journal on Arabic Language and Literature, 2024)
Al-Farra’ is a major figure in the Kufah school of thought who made many contributions to Arabic grammar or nahwu. Al-Farra’s most famous work is the book Ma’ani al-Qur’an which is divided into three Juz/parts. The uniqueness of the book Ma’ani al-Qur’an is that it is a book of interpretation which has a nahwu style, and in each surah not all verses are written. Therefore, it will be very interesting to explore and uncover the contents of the book Ma’ani al-Qur’an by al-Farra’. The method used in this study is descriptive-qualitative, with the material object used being the book Ma’ani al-Qur’an juz 3 in the surah al-Mulk. The results of the study show that of the 11 verses of surah al-Mulk, there are 8 verses that are the subject of debate among experts and the pure thoughts of al-Farra’. In his thinking, al-Farra’ always considers the diction of word forms so as not to change the essence of the meaning of the text contained in the verses of the Qur’an. In addition, he tends to use the principles of ta’wil (interpretation), qiyas (analogy), ijma’, and lughah (eloquent language) in his ushul (principles) of nahwu.